Assessing Climate Change Adaptation and Risk Management Programmes: Stakeholder Participation Process and Policy Implications for Transport, Energy and Tourism Sectors on the Island of Sicily - Carmelo J. Leon; Yen E. Lam González; Giovanni Ruggieri; Patrizia Calò (Land, 2022)
Climate change is a critical sustainability challenge for islands and their main economic sectors. Rising sea levels, extreme temperatures, and drier conditions are the impacts with the most significant potential to amplify the economic damage on islands. However, their isolation and natural conditions bring about some leeway to respond to climate impacts on their terms. This paper aims to provide a local-level analysis and ranking of alternative adaptation pathways in an island context through the stakeholders’ lens. This study reviews the latest advancements in adaptation science and proposes a catalogue of adaptation and risk management options that feed a participatory assessment and ranking by local stakeholders. The research was conducted on the island of Sicily (Italy) and saw the participation of high-level experts and tourism, energy, and maritime transport representatives. It employs a sequential process of four ordered steps oriented towards adaptation planning and stakeholders’ engagement. The process reveals breaches between what stakeholders’ would prioritise when designing policy pathways and their opinion about the most beneficial and balanced adaptation programmes across the sustainability criteria. Results indicate that, according to stakeholders, the priorities are to prepare the energy, tourism, and maritime transport sectors to confront future climate-related events more efficiently. Other transformational actions to ensure long-term social-ecological resilience, which requires significant structural changes and substantial investments, are not at the core of the public needs.